Total Ankle Arthroplasty Historical Overview, Current Concepts and Future Perspectives - Hintermann, Beat (Springer Vienna : Imprint: Springer, 2005)
Increasing success of arthroplasty of joints like the hip and knee along with concerns about the long-term outcomes of ankle arthrodesis has renewed interest in ankle arthroplasty. The new implants have been designed with attention to reproducing normal ankle anatomy, joint kinematics, ligament stability, and mechanical alignment. This publication will be the first comprehensive atlas on this topic and offers a unique physiological and mechanical characteristics of the ankle joint and of the selected total ankle system. Furthermore it will greatly enhance one's knowledge of this dynamic field and stimulate the scientific approach to management of end-stage arthritis of the ankle. It reflects the author's accumulated experience of the last decade with extended laboratory work on biomechanics of the ankle joint complex and more than 350 total ankle procedures. The atlas is well illustrated with many impressive figures, drawings and coloured pictures.